Kemas Ulang Informasi Gambir untuk Meningkatkan Perekonomian Masyarakat di Pangkalan Kabupaten 50 Kota - Wulandari, Putri; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractThe purpose of this paper is to write gambir information to improve the economy of communities in the County Town 50 Bases. This paper aims at 1. to describe how the potential of the information society economy boost in Gambier in 50 Districts of the city, Base 2. to describe the down gambir information in improving the economy of communities in the County Town 50 Bases. Data collected through observation and interviews with farmers Gambier at the base 50 District of the city. Penganalisisan descriptive data is carried out.Based on the research it can be concluded the following things. The first information creation of this information is to inform the potential and processing of gambier to improve the economy of the people in the Regency 50 City Base, in order to get the potential of quality gambir, it is necessary to pay attention to the gambir leaves and twigs to be processed and the fertilizers used and cleaning (weeding) in the gambir agar area gambir leaves and twigs that will be processed avoid other plants such as parasites that can affect the gambier leaves and gambir twigs that will be processed can not produce or remove a lot of sap when processed, gambier plants will also produce a lot of sap when the gambier plant faces with sunlight light processing gambir in the following way; (1) Harvesting of gambir leaves, (2) Transportation of gambier leaves in the house of felts, (3) Boiling, (4) Extraction / Pressing, (5) Deposition, (6) Draining, (7) Printing, (8) and Drying.Keywords: Gambier, the economy of the community, and the selling price, the processing of Gambier.